A Scoping Review of the Quality and the Design of Evaluations of Mobile Health, Telehealth, Smart Pump and Monitoring Technologies Performed in a Pharmacy-Related Setting - Baines, Darrin; Gahir, Imandeep K.; Hussain, Afthab; Khan, Amir J.; Schneider, Philip; Hasan, Syed S.; Babar, Zaheer-Ud-Din (Frontiers in Pharmacology, 2018)
Background: There is currently a need for high quality evaluations of new mobile health, telehealth, smart pump and monitoring technologies undertaken in a pharmacy-related setting. We aimed to evaluate the use of mobile health, telehealth, smart pump and monitoring technologies performed in a pharmacy-related setting. Methods: A systematic searching of English articles that examined the quality and the design of technologies conducted in pharmacy-related facilities was performed using the following databases: MEDLINE and Cumulative index to Nursing and Allied Health Literature (CINAHL) to identify original studies examining the quality and the design of technologies and published in peer-reviewed journals. Extraction of articles and quality assessment of included articles were performed independently by two authors. Quality scores over 75% are classed as being acceptable using a "relatively conservative" quality benchmark. Scores over 55% are included using a "relatively liberal" cut-off point. Results: Screening resulted in the selection of 40 formal evaluations. A substantial number of studies (32, 80.00%) was performed in the United States, quantitative in approach (33, 82.50%) and retrospective cohort (24, 60.00%) in study design. The most common pharmacy-related settings were: 22 primary care (55.00%); 10 hospital pharmacy (25.00%); 7 community pharmacy (17.50%); one primary care and hospital pharmacy (2.50%). The majority of the evaluations (33, 82.50%) reported clinical outcomes, six (15.00%) measured clinical and economic outcomes, and one (2.50%) economic only. Twelve (30.00%) quantitative studies and no qualitative study met objective criteria for "relatively conservative" quality. Using a lower "relatively liberal" benchmark, 27 quantitative (81.82%) and four qualitative (57.41%) studies met the lower quality criterion. Conclusion: Worldwide, few evaluations of mobile health, telehealth, smart pump and monitoring technologies in pharmacy-related setting have been published. Their quality is often below the standard necessary for inclusion in a systematic review mainly due to inadequate study design. Keywords: Pharmacy, pharmaceutical care, mobile health, telehealth, smart pumps, monitoring technologies